Effects of CT section thickness and reconstruction kernel on emphysema quantification relationship to the magnitude of the CT emphysema index - Gierada, David S; Bierhals, Andrew J; Choong, Cliff K; Bartel, Seth T; Ritter, Jon H; Das, Nitin A; Hong, Cheng; Pilgram, Thomas K; Bae, Kyongtae T; Whiting, Bruce R; Woods, Jason C; Hogg, James C; et al. (Academic radiology, 2010)
Computed tomography (CT) section thickness and reconstruction kernel each influence CT measurements of emphysema. This study was performed to assess whether their effects are related to the magnitude of the measurement. Low-radiation-dose multidetector CT was performed in 21 subjects representing a wide range of emphysema severity. Images were reconstructed using 20 different combinations of section thickness and reconstruction kernel. Emphysema index values were determined as the percentage of lung pixels having attenuation lower than multiple thresholds ranging from -960 HU to -890 HU. The index values obtained from the different thickness-kernel combinations were compared by repeated measures analysis of variance and Bland-Altman plots of mean versus difference in all subjects, and correlated with quantitative histology (mean linear intercept, Lm) in a subset of resected lung specimens. The effects of section thickness and reconstruction kernel on the emphysema index were significant (P < .001) and diminished as the index attenuation threshold was raised. The changes in index values from changing the thickness-kernel combination were largest for subjects with intermediate index values (10%-30%), and became progressively smaller for those with lower and higher index values. This pattern was consistent regardless of the thickness-kernel combinations compared and the HU threshold used. Correlations between the emphysema index values obtained with each thickness-kernel combination and Lm ranged from r = 0.55-0.68 (P = .007-.03). The effects of CT section thickness and kernel on emphysema index values varied systematically with the magnitude of the emphysema index. All reconstruction techniques provided significant correlations with quantitative histology.